2022
DOI: 10.1001/jamanetworkopen.2022.48826
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fluid Balance With Short- and Long-term Respiratory Outcomes in Extremely Premature Neonates

Abstract: ImportanceExtremely low gestational age neonates are at risk of disorders of fluid balance (FB), defined as change in fluid weight over a specific period. Few data exist on the association between FB and respiratory outcomes in this population.ObjectiveTo describe FB patterns and evaluate the association of FB with respiratory outcomes in a cohort of extremely low gestational age neonates.Design, Setting, and ParticipantsThis study is a secondary analysis of the Preterm Erythropoietin Neuroprotection Trial (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…32,33 Since that adoption, opportunities for improvement in the modified, neonatal KDIGO definition have been identified, including but not limited to gestational age-varying SCr thresholds, failure of SCr level to decline after birth, fluidcorrected SCr level, and ideal UOP criteria. [34][35][36] We acknowledge that ideal criteria to differentiate between continuation of an initial AKI episode vs a new (and thus recurrent) AKI episode should be further elucidated, and the determination of an optimal and standardized definition of rAKI is still needed. The present study raises important questions about rAKI, such as the timing of greatest risk and the importance of duration of AKI, which may help signify the impact of injury.…”
Section: Jama Network Open | Nephrologymentioning
confidence: 99%
“…32,33 Since that adoption, opportunities for improvement in the modified, neonatal KDIGO definition have been identified, including but not limited to gestational age-varying SCr thresholds, failure of SCr level to decline after birth, fluidcorrected SCr level, and ideal UOP criteria. [34][35][36] We acknowledge that ideal criteria to differentiate between continuation of an initial AKI episode vs a new (and thus recurrent) AKI episode should be further elucidated, and the determination of an optimal and standardized definition of rAKI is still needed. The present study raises important questions about rAKI, such as the timing of greatest risk and the importance of duration of AKI, which may help signify the impact of injury.…”
Section: Jama Network Open | Nephrologymentioning
confidence: 99%
“…Thus, extremely small, preterm infants have relatively high IWL (expressed ml/kg) due to an increased ratio of surface area to body weight, immature skin, and greater skin blood flow (Fig. 2) [10 ]. A primary factor regulating IWL is the humidity of the environment.…”
Section: Insensible Water Lossesmentioning
confidence: 99%
“…With this study, Starr and colleagues add to the growing body of literature recognising the importance of fluid status in neonates 1–3 . Utilising the weight‐change method for estimating fluid balance, which is the preferred method in neonates, 4 they found that fluid balance is independently associated with the need for mechanical ventilation at post‐natal day 14 and the composite outcome of severe bronchopulmonary dysplasia (BPD) or death.…”
mentioning
confidence: 93%